Agile and adaptive governance in crisis response: Lessons from the COVID-19 pandemic. (December 2020) - Janssen, Marijn; van der Voort, Haiko
Highlights: Adaptive governance requires oscillation between decentral and central decision-making structures. Agility can hinder adaptability. Bureaucracy and adaptability can go hand in hand. Agile and adaptive governance are not the same. Technology might hinder adaptiveness. Abstract: Countries around the world have had to respond to the COVID-19 outbreak with limited information and confronting many uncertainties. Their ability to be agile and adaptive has been stressed, particularly in regard to the timing of policy measures, the level of decision centralization, the autonomy of decisions and the balance between change and stability. In this contribution we use our observations of responses to COVID-19 to reflect on agility and adaptive governance and provide tools to evaluate it after the dust has settled. Whereas agility relates mainly to the speed of response within given structures, adaptivity implies system-level changes throughout government. Existing institutional structures and tools can enable adaptivity and agility, which can be complimentary approaches. However, agility sometimes conflicts with adaptability. Our analysis points to the paradoxical nature of adaptive governance. Indeed, successful adaptive governance calls for both decision speed and sound analysis, for both centralized and decentralized decision-making, for both innovation and bureaucracy, and both science and politics.